PENGARUH MOTIVASI KERJA TERHADAP KINERJA KARYAWAN DENGAN KOMIMEN ORGANISASI SEBAGAI VARIABLE MODERASI: (Studi Kasus Perusahaan Manufaktur di Bandung) - Baihaqi, Muhammad Iqbal; Paulus, Aditya Christian (JURISMA : Jurnal Riset Bisnis & Manajemen, 2020)
Human Resource Management have a crucial role in improving employee performance in a company. A company needs to continuously improve their employees’s performance. The influence of motivation and moderation of commitment plays an important role in improving performance. PT x is a labor intensive company which operates in clothing production and export. This research conducted at PT x aims to find out how much influence Motivation has on performance which is partially and simultaneously moderated by employee commitment. This research uses two methods, which is Descriptive Method and Verification Method. The sample for this research are 100 employees whom are chosen randomly. The study concluded that performance is said to be good and motivation is said to be good commitment and motivation on performance which is moderated by employee commitment has a significant effect on both partial and simultaneous performance.